The Art of Arabic Instruction for Students in Primary Stage - Syafaah, Daris (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2017)
The objectives of language instruction are informing students with skills that are generally desired. All stages of education have a standard compentence that must be achieved by the teacher. The primary stage is stage for students aged 7-12. They have different characteristics depend on students in higher level. So, the teacher has to pay attention for students when teach Arabic language in this stage.  They must be creative in teaching Arabic language based on teacher’s ability, method, learning strategy, and learning media that are suitable with students caracteristic (students at primary stage).